Diversity in boron toxicity tolerance of Australian barley (Hordeum vulgare L.) genotypes. Issue 1 (December 2015) - Hayes, Julie; Pallotta, Margaret; Garcia, Melissa; Öz, Mehmet; Rongala, Jay; Sutton, Tim
Abstract Background Boron (B) is an important micronutrient for plant growth, but is toxic when levels are too high. This commonly occurs in environments with alkaline soils and relatively low rainfall, including many of the cereal growing regions of southern Australia. Four major genetic loci controlling tolerance to high soil B have been identified in the landrace barley, Sahara 3771. Genes underlying two of the loci encode the B transportersHvBot1 andHvNIP2;1 . Results We investigated sequence and expression level diversity inHvBot1 andHvNIP2;1 across barley germplasm, and identified five novel coding sequence alleles forHvBot1 . Lines were identified containing either single or multiple copies of the SaharaHvBot1 allele. We established that only the tandemly duplicated Sahara allele conferred B tolerance, and this duplicated allele was found only in a set of nine lines accessioned in Australian collections as Sahara 3763–3771.HvNIP2;1 coding sequences were highly conserved across barley germplasm. We identified the likely causative SNP in the 5'UTR of SaharaHvNIP2;1, and propose that the creation of a small upstream open reading frame interferes with HvNIP2;1 translation in Sahara 3771. Similar toHvBot1, the tolerantHvNIP2;1 allele was unique to the Sahara barley accessions. We identified a new source of the 2H B tolerance allele controlling leaf symptom development, in the landrace Ethiopia 756. Conclusions Ethiopia 756, as well as the cultivar Sloop Vic which carries both the 2H andHvBot1 B tolerance alleles derived from Sahara 3771, may be valuable as alternative parents in breeding programs targeted to high soil B environments. There is significant diversity in B toxicity tolerance among contemporary Australian barley varieties but this is not related to variation at any of the four known B tolerance loci, indicating that novel, as yet undiscovered, sources of tolerance exist.